Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41541-019-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing yellow fever immunity impairs and modulates the antibody response to tick-borne encephalitis vaccination

Abstract: Flaviviruses have an increasing global impact as arthropod-transmitted human pathogens, exemplified by Zika, dengue, yellow fever (YF), West Nile, Japanese encephalitis, and tick-borne encephalitis (TBE) viruses. Since all flaviviruses are antigenically related, they are prone to phenomena of immunological memory (‘original antigenic sin’), which can modulate immune responses in the course of sequential infections and/or vaccinations. In our study, we analyzed the influence of pre-existing YF vaccine-derived i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 51 publications
2
34
1
Order By: Relevance
“…However, there are also indications that the quality of antibodies can be impeded by prior flavivirus immunity. For example, in one study, individuals pre-vaccinated against YFV were shown to have a lower ratios of neutralizing to ELISA antibody titers (70), emphasizing that the quality of immune responses and not only the magnitude are important in determining the potential of cross-reactive immunity to induce protection versus pathology (Figure 2).…”
Section: Flavivirus Cross-reactive Antibody Responsesmentioning
confidence: 99%
“…However, there are also indications that the quality of antibodies can be impeded by prior flavivirus immunity. For example, in one study, individuals pre-vaccinated against YFV were shown to have a lower ratios of neutralizing to ELISA antibody titers (70), emphasizing that the quality of immune responses and not only the magnitude are important in determining the potential of cross-reactive immunity to induce protection versus pathology (Figure 2).…”
Section: Flavivirus Cross-reactive Antibody Responsesmentioning
confidence: 99%
“…The flavivirus E proteins used in this study (Table 1) were produced with the Drosophila expression system (Invitrogen) as described previously [40,[43][44][45]. The expression vector pT389 (kindly provided by Thomas Krey and Felix Rey, Institute Pasteur, France), encoding the E gene lacking the stem-anchor region (synthesized by GeneArt/Thermo Fisher Scientific, Table 1), an enterokinase cleavage site and a double strep-tag (C-terminal), was transfected into Drosophila S2 cells by CaCl 2.…”
Section: Recombinant Antigensmentioning
confidence: 99%
“…Broadly cross-reactive antibody responses are also known for other enveloped RNA viruses, which may positively or negatively affect subsequent infection or vaccination. Flaviviruses for example, are antigenically related and broadly flavivirus cross-reactive antibodies from previous yellow fever vaccination has been shown to impair and modulate immune responses to tick-borne encephalitis vaccination [65]. Similarly, immune history has been shown to profoundly affect protective B cell responses to influenza [66].…”
Section: Discussionmentioning
confidence: 99%